Lux Navitas - Ali, Rodilah; Ahlip, Farah Nur Filza; Boni, Leslie; Ag Salleh, Nur Hafizah (2015)
Established in 3 June 2012, Lux Navitas a partnership company with four (4) partners which is the Chief Executive Officers and Marketing Manager is Miss Rodilah Binti Ali, Financial Manager is hold by Miss Farah Nur Filza Binti Ahlip, Operatioan Manager is hold by Miss Nurhafizah Binti Ag Salleh and last partners is Miss Leslie Binti Boni which holding position as Administrative Manager. Lux Navitas got its name from a latin name which means 'light energy'. We choose to use light energy because based on our product itselfthe bulb that produce light and energy means the product that can save the energy. Lux Navitas is electricity shop that located in Kota Kinabalu, Sabah. Lux Navitas is a company that sell product based on infrared sensor. While there are many others bulb that similar function that can save energy but Lux Navitas offers slightly different items which installed with infrared sensor which make the bulb function when someone is around. The infrared sensor is functioning to detect the absence of moving things and will be switch off automatica11y when there is no movement detected. With the instaJlation of the infrared sensor, we believe that our product can get into the market easily. Location of Lux Navitas store in the middle of the city will allow it to attract a lot of customers' attraction. Lux Navitas has foreseen this opportunity to offer a better product to help to save power, energy and money also to save the earth. Other than that, Lux Navitas saw the opportunity that this business has the potential of success in this industry with some exposure to society through advertisement which functioning as a whistleblower to spread about the existence of this product to society. While promoting and exposing this product to society, we, on the same time help the customers aware about the importance saving the power and energy to help to reduce and prevent the global warming from getting worsen.